PEMBELAJARAN MENGANALISIS STRUKTUR TEKS ANEKDOT DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENTS TEAM ACHIEVEMENTS DIVISION (STAD) - Siti Liantina Zulfa Khodijah; Neng Fitri Andriani; Via Nugraha (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the difficulty of students in analyzing anecdotal text structures. This happens because students lack an understanding of the explanation of learning material caused by students' lack of focus when listening and lacking interest in reading. The formulation of the problem from this study is, is there a difference in the results of the posttest of learning analyzing the anecdotal text structure between the experimental classes applied by the STAD model and the control class that is applied to the discovery learning model? The purpose of this study was to find out the differences in students' abilities in analyzing anecdotal text structures using the STAD model with those using discovery learning models. This study used a quasi-experimental research method with a posttest-only control design research design. The research sample is one class as the experimental class and the other class as the control class. The research instrument used was the test sheet. The results showed that there were significant differences between the two classes. The average value in the control class is 53.0 with the smallest value of 20 and the highest value of 100. While the experimental class obtained the average value of 79.4 with the smallest value 0 and the highest value of 100. The results of the normality test using SPSS shows that the significance of 0.423. The results show that the data is homogeneous because the significance value is> 0.05, which is 0.436. The results of the T-test obtained a value of 0,000 <0.05. These results indicate that there are significant differences between the two samples.